Analysıs on Lıfe Satısfactıon of Swımmers - Özgür Karataş; Serdar Şahin (Türk Spor ve Egzersiz Dergisi)
The purpose of this study is to analyze the life satisfaction of swimmers at the age group of 13-14 in Eastern and Southeastern Anatolia Region. General screening model, which is one of the descriptive methods, was used in the research. Research contains a total of 131 swimmers composed of 50 females and 81 males at the age group of 13-14 competing in semi-final of 2017-2018 Anatolian Stars League Eastern and Southeastern Anatolia Region held in Van province. As the data collection tool, “Life Satisfaction Scale” developed by Diener, Emmons, Laresen and Griffin (9) and adopted into Turkish by Köker (25) and Yetim (34) was used in the study. The scale is a self-evaluation 5-point Likert-type scale ranging from 1 (absolutely inappropriate) to 7 (absolutely appropriate). The value of .95 was found as Cronbach Alpha coefficient belonging to the life satisfaction scale of the participant swimmers. In the evaluation of the data of the study, frequency, percentage, mean and standard deviation among the descriptive statistical methods were used and t test was applied for pairwise groups and post-hoc scheffe test was applied after Anova test for multiple groups. It has been determined that “Life Satisfaction Scale” of swimmers participating in our study display statistically significant differences by the variables of sex, age, the grade studied and monthly income (p lt;.05). It has been concluded following the research that the variables of sex, age, grade studied and monthly income are important variables affecting the life satisfaction of swimmers the age group of 13-14.